Options for deformable segmental lining systems for tunnelling in squeezing rock. (June 2018) - Mezger, F.; Ramoni, M.; Anagnostou, G.
Highlights: Technical and economical evaluation of deformable segmental linings. Discussion about radially and tangentially deformable linings. Development of design aids for practical application. Structural and cost comparison: resistance vs. yielding principle. Abstract: The rock pressure developing when shield tunnelling through squeezing rock may damage the segmental lining. This paper analyses the extent to which the application range of shielded TBMs in squeezing rocks might be widened by using deformable lining systems, while considering the aspects of structural safety, construction management, TBM technologies and construction costs. Deformable lining systems exploit a basic feature of squeezing ground: the rock pressure decreases when deformations are allowed to occur. Two basic options are available: radially deformable linings, where rock deformations occur outside the lining extrados; and tangentially deformable linings which can accommodate a reduction in their circumference. Comparative analyses of radially or tangentially deformable linings and conventional, practically rigid segmental linings show that deformable lining systems offer advantages only for deep tunnels crossing rocks of relatively fair quality. In such cases, rock pressure can be decreased significantly by allowing deformations to occur, so that a deformable lining (particularly, a tangentially deformable one) offers a more effective use of the available bored profile than a thicker stiff lining of the same concrete quality.